Adhesive composition

By introducing ester or ether-based dianhydride compounds and dimer acids into the polyimide-based resin, combined with epoxy resin, combined with phosphorus-based flame retardant, the adhesiveness and insulation in flexible printed circuit boards are solved. The lack of reliability and solder heat resistance achieves excellent performance in narrow pitch wiring and high magnetic coil applications.

CN119317682APending Publication Date: 2025-01-14TOYOBO MC CORP +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380045192.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-28
Filing Date
2023-09-22
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In the prior art, when the polyimide-based resin used in flexible printed circuit boards is used as the adhesive, it is difficult to satisfy the adhesiveness, insulation reliability and solder heat resistance at the same time, especially in narrow pitch wiring and high magnetic coils. There are challenges in the application.

Method used

By introducing dianhydride compounds with ester or ether groups and dimeric acids as structural units of polyimide-based resins and combining them with epoxy resins, the fluidity and welding heat resistance of the adhesive are improved, and the phosphorus-based system is combined with the epoxy resin. Flame retardant to improve insulation reliability.

Benefits of technology

It realizes excellent performance of adhesiveness, insulation reliability and solder heat resistance in flexible printed circuit board applications, and is suitable for use in narrow pitch wiring and high magnetic coil covering films and adhesive films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005172072850000101
    Figure BDA0005172072850000101
  • Figure BDA0005172072850000171
    Figure BDA0005172072850000171
  • Figure BDA0005172072850000181
    Figure BDA0005172072850000181
Patent Text Reader

Abstract

Provided is an adhesive composition which is suitable for use in a flexible printed wiring board, and which sufficiently satisfies adhesiveness, insulation reliability, and solder heat resistance. The adhesive composition is characterized by containing an imide group-containing resin (A) and an epoxy resin (B), and the imide group-containing resin (A) contains a dianhydride compound (C) having an ester group or an ether group and a dimer acid (D) as structural units. The adhesive composition according to the present invention may further contain a phosphorus-based flame retardant (E). The adhesive composition according to the present invention is particularly suitable for use in flexible printed wiring boards such as copper clad laminates, cover layer films, adhesive sheets, and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive composition comprising a polyimide resin and a curing agent, and more particularly to an adhesive composition having excellent adhesion, insulation reliability and solder heat resistance and suitable for use in flexible printed circuit boards such as copper clad laminates, coverlay films and adhesive sheets. Background Art

[0002] Flexible printed circuit boards are widely used as circuit substrates for electronic devices that require flexibility and space saving, such as smartphones, tablets, digital cameras, etc. As the number of components mounted on devices increases due to miniaturization and higher performance, flexible printed circuit boards are required to form wiring with narrower pitches than before.

[0003] As a material used in flexible printed circuit boards, polyimide resins are mentioned. Polyimide resins are mainly synthesized from aromatic monomers and are used as base films for copper-clad laminates and coverlay films because they exhibit high heat resistance, insulation reliability, and mechanical strength.

[0004] On the other hand, adhesives are required in copper-clad laminates for laminating base films and copper foil wiring, cover films for protecting circuits, and adhesive sheets for laminating substrates. According to their production processes, thermosetting adhesives are used, but polyimide resins composed of aromatic monomers have a high glass transition temperature and are therefore difficult to laminate by conventional hot pressing, making them difficult to use as adhesives.

[0005] Therefore, a method of using polyimide resin as an adhesive while maintaining its characteristics such as heat resistance, insulation reliability, and mechanical strength is being discussed. A method of copolymerizing long-chain monomers and oligomers such as aliphatic to impart fluidity and flexibility during bonding and then combining it with a curing agent is being discussed.

[0006] Patent Document 1 proposes a modified polyamideimide of a polyimide-based resin in which a siloxane having an amine as a reactive functional group is introduced into a molecular chain terminal, and uses the modified polyamideimide as a main agent of an adhesive.

[0007] Furthermore, Patent Document 2 proposes a modified polyamideimide of a polyimide-based resin of acrylonitrile-butadiene rubber having a carboxylic acid as a reactive functional group introduced into a molecular chain terminal, and uses the modified polyamideimide as a main agent of an adhesive. Prior art literature Patent Literature

[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 2005-179513 Patent Document 2: Japanese Patent No. 3931387 Summary of the invention Problem that the invention aims to solve

[0009] The polyimide resin with the siloxane structure introduced in the patent document 1 needs to use a very expensive starting material with a siloxane bond in order to give the flexibility that can be used as an adhesive, which is relatively poor in economy. In addition, with the increase in the amount of the siloxane structure introduced, there is a worry that the resin adhesion is reduced. In addition, in order to use the modified polyamide-imide recorded in the patent document 2 to show sufficient adhesion, it is necessary to increase the amount of acrylonitrile-butadiene rubber introduced, as a result, due to the hygroscopic effect caused by the nitrile group in the acrylonitrile-butadiene rubber, the insulation reliability decreases, so it is difficult to be used for narrow spacing wiring. Therefore, from the perspective of the use of flexible printed circuit boards, a polyimide resin that can be used as an adhesive is desired, but in the prior art, it is not possible to obtain a resin that fully satisfies adhesion and insulation reliability at the same time.

[0010] The present invention has been made to solve the above-mentioned problems of the prior art, and an object thereof is to provide an adhesive composition suitable for use in flexible printed wiring boards and fully satisfying adhesion, insulation reliability, and solder heat resistance. Means to solve problems

[0011] The present inventors have conducted intensive studies to achieve the above-mentioned object and have found that, even without using a highly hygroscopic raw material such as acrylonitrile-butadiene rubber, by introducing a dimer acid as a long-chain monomer constituting a polyimide resin and further introducing a dianhydride compound having an ester group or an ether group, fluidity and softness during bonding can be imparted. As a result, an adhesive composition combining such a polyimide resin and an epoxy resin can solve the above-mentioned problems, thereby completing the present invention.

[0012] That is, the present invention is constituted by the following [1] to [9]. [1] An adhesive composition comprising an imide group-containing resin (A) and an epoxy resin (B), wherein the imide group-containing resin (A) contains a dianhydride compound (C) having an ester group or an ether group and a dimer acid (D) as structural units. [2] The adhesive composition according to [1], wherein the dianhydride compound (C) is alkylene glycol bis(trimellitic anhydride). [3] The adhesive composition according to [1], wherein the dianhydride compound (C) is 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride or oxydiphthalic anhydride. [4] An adhesive composition according to any one of [1] to [3], characterized in that the copolymerization amounts of the dianhydride compound (C) and the dimer acid (D) are each in the range of 1 to 80 mol %, based on 100 mol % of the total polycarboxylic acid component constituting the imide group-containing resin (A). [5] The adhesive composition according to any one of [1] to [3], further comprising a phosphorus-based flame retardant (E). [6] A copper-clad laminate comprising a copper foil laminated on at least one surface of an insulating plastic film via the adhesive composition described in any one of [1] to [3]. [7] A coverlay film, characterized by being formed by laminating an adhesive layer comprising the adhesive composition according to any one of [1] to [3] and an insulating plastic film. [8] An adhesive sheet comprising a laminate of an adhesive layer comprising the adhesive composition according to any one of [1] to [3] and a removable protective film. [9] A flexible printed wiring board comprising a layer comprising the adhesive composition according to any one of [1] to [3]. Effects of the Invention

[0013] The adhesive composition of the present invention can simultaneously exhibit excellent adhesion, high insulation reliability and solder heat resistance. Therefore, the adhesive composition of the present invention can be preferably used as an adhesive for a flexible printed circuit board. In particular, since the adhesive composition of the present invention has high insulation reliability after curing and high fluidity before curing, it can be preferably used as a cover layer film and a laminated adhesive film for a flexible printed circuit board with a narrow wiring spacing between circuits or a flexible printed circuit board with a coil exhibiting a strong magnetic force. DETAILED DESCRIPTION

[0014] Hereinafter, embodiments of the present invention will be described in detail, but the present invention is not limited thereto.

[0015] The adhesive composition of the present invention contains an imide group-containing resin (A) and an epoxy resin (B), and further contains a flame retardant as needed, and the imide group-containing resin (A) is characterized in that it contains a dianhydride compound (C) having an ester group or an ether group (hereinafter also referred to as a dianhydride compound (C) or simply referred to as component (C)) and a dimer acid (D) as structural units.

[0016] <Imido group-containing resin (A)> The imide group-containing resin (A) refers to a resin having an imide group as a repeating unit, that is, a so-called polyimide resin, and may have other groups such as an amide group, a urethane group, an ester group, and an ether group as a repeating unit in addition to the imide group.

[0017] <Dianhydride compound (C)> When the obtained imide group-containing resin (A) is used as an adhesive composition, the polarity of the ester group or ether group of the dianhydride compound (C) can enhance the interaction between the adhesive and the adherend surface, thereby achieving a stronger bonding strength. In addition, as a result, it is also less likely to peel or bulge in the solder heat resistance evaluation.

[0018] As the dianhydride compound (C) having an ester group, for example, ethylene glycol bis-trimellitic anhydride, propylene glycol bis-trimellitic anhydride, 1,4-butanediol bis-trimellitic anhydride, hexamethylene glycol bis-trimellitic anhydride, polyethylene glycol bis-trimellitic anhydride, polypropylene glycol bis-trimellitic anhydride and other alkylene glycol bis-trimellitic anhydride can be mentioned. In addition, as the dianhydride compound (C) having an ether group, for example, 4,4'-(4,4'-isopropylidene diphenyloxy) diphthalic anhydride, oxydiphthalic anhydride and the like can be mentioned. In addition, a compound hydrogenated from any one of these compounds can also be used. These can be used alone or in combination. Taking the total amount of polycarboxylic acid components constituting the imide group-containing resin (A) as 100 mol%, the copolymerization amount of the (C) component is preferably 1 to 80 mol%, more preferably 10 to 60 mol%, and further preferably 15 to 50 mol%. When the copolymerization amount of the component (C) is less than the above lower limit, the adhesiveness may be deteriorated. When it is more than the above upper limit, the raw material price may increase, which may be industrially disadvantageous.

[0019] <Dimer Acid (D)> The dimer acid (D) is a dicarboxylic acid having 36 carbon atoms produced by dimerizing an unsaturated fatty acid having 18 carbon atoms. As the dimer acid (D), a dicarboxylic acid in which the unsaturated bond is hydrogenated may be used.

[0020] When using a polyimide resin based on aromatics, it lacks fluidity and flexibility in the adhesive laminating process, and as a result, it is difficult to obtain sufficient bonding strength. The imide-containing resin (A) used in the present invention is copolymerized with dimer acid (D) as a structural unit, and its aliphatic chain gives fluidity and flexibility, and can fill the surface unevenness of the adherend during hot pressing, and as a result, the adhesion can be improved. When the total polycarboxylic acid component amount constituting the imide-containing resin (A) is 100 mol%, the copolymerization amount of dimer acid (D) is preferably 1 to 80 mol%, more preferably 10 to 70 mol%, and further preferably 30 to 60 mol%. When the copolymerization amount of dimer acid (D) is less than the above lower limit, there is a concern that the adhesion deteriorates; when it is more than the above upper limit, there is a concern that the imide-containing resin cannot obtain good heat resistance.

[0021] The imide-containing resin (A) may also have a polycarboxylic acid component other than the above-mentioned (C) component and dimer acid (D). As such a polycarboxylic acid component, from the viewpoint of improving the heat resistance of the obtained imide-containing resin (A) and the adhesive composition, it is preferred to use a polycarboxylic acid component with an aromatic ring. As a polycarboxylic acid component with an aromatic ring, for example, trimellitic anhydride, pyromellitic dianhydride, benzophenone tetracarboxylic dianhydride, biphenyl tetracarboxylic dianhydride, naphthalene tetracarboxylic dianhydride, diphenyl sulfone tetracarboxylic dianhydride, perylene tetracarboxylic dianhydride, (hexafluoroisopropylidene) diphthalic anhydride, terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, etc. These can be used alone or in combination. From the balance of heat resistance, flexibility and adhesive strength, the copolymerization amount of the polycarboxylic acid component having an aromatic ring is preferably 20 to 90 mol%, more preferably 30 to 80 mol%, and further preferably 40 to 70 mol%, based on the total polycarboxylic acid component amount constituting the imide group-containing resin (A) as 100 mol%. It should be noted that when the dianhydride compound (C) has an aromatic ring, it is also included in the calculation.

[0022] Among them, as a polycarboxylic acid component, in addition to the polycarboxylic acid component with an aromatic ring that has been described, aliphatic or alicyclic polycarboxylic acids or monoanhydrides or dianhydrides of polycarboxylic acids can also be used within the scope of not damaging the effect of the present invention. For example, it can be mentioned: a component that hydrogenates any one of the above-mentioned polycarboxylic acid components with an aromatic ring, meso-butane-1,2,3,4-tetracarboxylic dianhydride, pentane-1,2,4,5-tetracarboxylic dianhydride, cyclobutane tetracarboxylic dianhydride, cyclopentane tetracarboxylic dianhydride, cyclohexane-1-ene-2,3,5,6-tetracarboxylic dianhydride, cyclohexane dicarboxylic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecane dioic acid, dodecanedioic acid, 2-methylsuccinic acid, etc. These can be used alone or in combination.

[0023] The imide group-containing resin (A) can be obtained by polymerizing a polycarboxylic acid component and an amine component or an isocyanate component as main raw materials. Among them, as the amine component, a compound having a difunctional or higher amino group can be used, and as the isocyanate component, a compound having a difunctional or higher isocyanate group can be used.

[0024] From the viewpoint of improving the heat resistance of the adhesive composition, the isocyanate component constituting the imide group-containing resin (A) preferably has an aromatic ring, and examples thereof include: diphenylmethane-4,4'-diisocyanate and its isomers, dimethyldiphenylmethane diisocyanate, diethyldiphenylmethane diisocyanate, dimethoxydiphenylmethane diisocyanate, diphenylether diisocyanate, benzophenone diisocyanate, diphenylsulfone diisocyanate, toluene diisocyanate, xylylene diisocyanate, naphthalene diisocyanate, 4,4'-[2,2-bis(4-phenoxyphenyl)propane] diisocyanate, dimethylbiphenyl diisocyanate, diethylbiphenyl diisocyanate, dimethoxybiphenyl diisocyanate, diethoxybiphenyl diisocyanate and their isomers, etc. In addition, as the amine component, a component in which the isocyanate group of the above-mentioned isocyanate component is substituted with an amino group can be cited. These may be used alone or in combination of multiple types.

[0025] In addition, as isocyanate components or amine components, in addition to the isocyanate components or amine components with aromatic rings that have been described, aliphatic or alicyclic isocyanate components or amine components can also be used within the scope that does not damage the effect of the present invention. For example, it can be mentioned: any hydrogenated component of the above-mentioned isocyanate components or amine components with aromatic rings, isophorone diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, ethylene diisocyanate, propylene diisocyanate, hexamethylene diisocyanate, etc., and as amine components, it can be mentioned that the isocyanate groups of these isocyanate components are replaced by amino groups. These can be used alone or in combination. From the viewpoint of heat resistance and flame retardancy of the adhesive composition using the obtained imide group-containing resin (A), the copolymerization amount of these components is preferably 50 mol% or less, and more preferably 20 mol% or less, based on 100 mol% of the total amount of the isocyanate component and the amine component.

[0026] In order to increase the reaction points with the curing agent and improve the heat resistance of the obtained adhesive composition, a compound having more than three functional groups can be copolymerized in the imide-containing resin (A). For example, it can be cited: polyfunctional carboxylic acids such as trimesic acid, dicarboxylic acids having hydroxyl groups such as 5-hydroxyisophthalic acid, dicarboxylic acids having amino groups such as 5-aminoisophthalic acid, compounds having more than three hydroxyl groups such as glycerol and polyglycerol, and compounds having more than three amino groups such as tris(2-aminoethyl)amine. When the total amount of polycarboxylic acid components or the total amount of isocyanate components and the total amount of amine components is taken as 100 mol%, the copolymerization amount is preferably less than 20 mol%. When it exceeds 20 mol%, there is a concern that gelation occurs during resin polymerization and insoluble matter is generated.

[0027] In the range that does not impair the effect of the present invention, the imide group-containing resin (A) may be copolymerized with polyester, polyether, polycarbonate, polysiloxane, etc. as a component that imparts flexibility to the obtained resin. In this case, since a large amount of copolymerization of these components in the imide group-containing resin (A) may impair heat resistance, insulation reliability, and economic efficiency, the copolymerization amount of these components is preferably 10 mol% or less, based on 100 mol% of the total polycarboxylic acid component amount or the total amount of the isocyanate component amount and the total amount of the amine component amount.

[0028] When the non-volatile components of the adhesive composition are 100% by mass, the content of the imide-containing resin (A) in the adhesive composition of the present invention is preferably 1 to 80% by mass, and more preferably 10 to 70% by mass. When the content of the imide-containing resin is too small, the high molecular weight component in the adhesive composition decreases, and there is a concern that it becomes brittle and difficult to handle. On the other hand, when the content of the imide-containing resin is too much, the proportion of the epoxy resin as a thermosetting component decreases, and the curing is insufficient, so there is a concern that the heat resistance decreases.

[0029] <Method for producing imide group-containing resin (A)> The imide group-containing resin (A) can be produced by a known method such as a method of reacting a polycarboxylic acid component with an isocyanate component (isocyanate method), a method of reacting a polycarboxylic acid component with an amine component to form an amic acid and then ring-opening the amic acid (direct method), or a method of reacting a compound having a carboxylic anhydride and a carboxylic acid chloride with an amine component (acid chloride method). Industrially, the isocyanate method is advantageous from the viewpoint of exhausting carbon dioxide as a by-product out of the system as a gas.

[0030] The following describes a typical method for producing the imide group-containing resin using an isocyanate method. However, the imide group-containing resin can also be produced similarly using the above-mentioned direct method or acid chloride method by using a corresponding amine component and a compound having a carboxylic acid chloride.

[0031] While the polycarboxylic acid component and the isocyanate component are heated to 60°C to 200°C in a solvent, the polymerization reaction of the imide group-containing resin (A) is carried out by stirring. At this time, the molar ratio of the polycarboxylic acid component / isocyanate component is preferably in the range of 90 / 100 to 100 / 90. It should be noted that, usually, the content (copolymerization amount) of the polycarboxylic acid component and the isocyanate component in the imide group-containing resin is the same as the ratio of each component during polymerization. In addition, in order to promote the reaction, alkali metals such as sodium fluoride, potassium fluoride, sodium methoxide, triethylenediamine, triethylamine, 1,8-diazabicyclo [5,4,0] -7-undecene, 1,5-diazabicyclo (4,3,0) -5-nonene, and catalysts such as dibutyltin dilaurate can be used. When these catalysts are too little, the target catalytic effect cannot be fully obtained; when they are too much, there is a possibility of causing side reactions. Therefore, based on 100 mol% of the larger polycarboxylic acid component or isocyanate component, it is preferably used in an amount of 0.01 to 5 mol%, more preferably 0.1 to 3 mol%.

[0032] As solvents that can be used for the polymerization reaction of the imide-containing resin (A), for example, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-butyl-2-pyrrolidone, γ-butyrolactone, dimethylimidazolidinone, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, cyclohexanone, cyclopentanone, etc. Among them, N-methyl-2-pyrrolidone or dimethylacetamide is preferred from the solubility of the obtained imide-containing resin and the goodness of the polymerization reaction efficiency. In addition, after the polymerization reaction, the solvent used in the polymerization reaction or other low boiling point solvents can be used for dilution to adjust the non-volatile component concentration and solution viscosity. These can be used alone or in combination.

[0033] Examples of the low boiling point solvent for dilution include aromatic solvents such as toluene and xylene, aliphatic solvents such as hexane, heptane and octane, alcohol solvents such as methanol, ethanol, propanol, butanol and isopropanol, ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone and cyclopentanone, ether solvents such as diethyl ether and tetrahydrofuran, and ester solvents such as ethyl acetate, butyl acetate and isobutyl acetate.

[0034] <Epoxy resin (B)> The adhesive composition of the present invention contains an epoxy resin (B). By using an imide-containing resin (A) in combination with an epoxy resin (B), the imide-containing resin (A) having excellent heat resistance can be enhanced to be fully adhered to the substrate by reaction with the epoxy resin (B), thereby imparting excellent solder heat resistance, and being suitable as an adhesive for flexible printed circuit boards.

[0035] As epoxy resin (B), silicone, polyurethane, polyimide, polyamide, etc. can be used for modification, and sulfur atoms, nitrogen atoms, etc. can also be contained in the molecular skeleton. As epoxy resin (B), for example, bisphenol-type epoxy resins such as bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, phenol novolac epoxy resin, cresol novolac epoxy resin, etc., phenolic novolac epoxy resin, hexahydrophthalic acid glycidyl ester, hydrogenated products of the above-mentioned bisphenol-type epoxy resins, hydrogenated products of the above-mentioned novolac epoxy resins, alicyclic epoxy resins such as glycidyl dimer acid, epoxidized polybutadiene, epoxidized soybean oil, etc. can be cited. These can be used alone or in combination. From the viewpoint of the heat resistance of the obtained cured product, the epoxy equivalent of epoxy resin (B) is preferably 100 to 300 g / eq, and more preferably 150 to 200 g / eq. The epoxy resin (B) preferably has an aromatic ring, and more preferably is a bisphenol-type epoxy resin or a novolac-type epoxy resin.

[0036] Examples of commercially available products of the epoxy resin (B) include bisphenol A epoxy resins such as jER828 and 1001 manufactured by Mitsubishi Chemical Corporation, hydrogenated bisphenol A epoxy resins such as ST-2004 and 2007 manufactured by Nippon Steel Chemical & Materials Co., Ltd., EXA-9726 manufactured by DIC Corporation, bisphenol F epoxy resins such as YDF-170 and 2004 manufactured by Nippon Steel Chemical & Materials Co., Ltd., jER152 and 154 manufactured by Mitsubishi Chemical Corporation, and Dow Chemical Co., Ltd. Phenol novolac epoxy resins such as DEN-438, dicyclopentadiene epoxy resins such as HP7200 and HP7200H manufactured by DIC Corporation, YDCN-700 series manufactured by Nippon Steel Chemicals & Materials Co., Ltd., cresol novolac epoxy resins such as EOCN-125S, 103S, and 104S manufactured by Nippon Kayaku Co., Ltd., flexible epoxy resins such as YD-171 manufactured by Nippon Steel Chemicals & Materials Co., Ltd., Epon1031S manufactured by Mitsubishi Chemical Corporation, BASF Araldite 0163 manufactured by Japan Co., Ltd., Denacol EX-611, EX-614, EX-622, EX-512, EX-521, EX-421, EX-411, EX-321 and other multifunctional epoxy resins manufactured by Nagase ChemteX Co., Ltd., Epikote 604 manufactured by Mitsubishi Chemical Corporation, YH-434 manufactured by Nippon Steel Chemical & Materials Co., Ltd., BASF Heterocyclic epoxy resins such as Araldite PT810 manufactured by Japan Co., Ltd., alicyclic epoxy resins such as CELLOXIDE 2021 and EHPE 3150 manufactured by Daicel Chemical Co., Ltd. and ERL 4234 manufactured by UCC, bisphenol S type epoxy resins such as EPIC LONE X A-1514 manufactured by DIC Corporation, triglycidyl isocyanurate such as TEPIC manufactured by Nissan Chemical Co., Ltd., bisxylenol type epoxy resins such as YX-4000 manufactured by Mitsubishi Chemical Corporation, bisphenol type epoxy resins such as YL-6056 manufactured by Mitsubishi Chemical Corporation, TETRAD-X and TETRAD-C manufactured by Mitsubishi Gas Chemical Co., Ltd., GAN manufactured by Nippon Kayaku Co., Ltd., and glycidylamine type epoxy resins such as ELM-120 manufactured by Sumitomo Chemical Co., Ltd.

[0037] When the non-volatile components of the adhesive composition are 100% by mass, the content of the epoxy resin (B) in the adhesive composition of the present invention is preferably 1 to 50% by mass, and more preferably 10 to 40% by mass. When the content of the epoxy resin is too small, sufficient thermosetting properties cannot be obtained, and as a result, there is a concern that the heat resistance of the adhesive composition is poor. When the content of the epoxy resin is too much, there is a concern that the flexibility of the adhesive composition is impaired, the bonding strength is reduced, and the insulation reliability is reduced due to impurities contained in the epoxy resin.

[0038] <Flame retardant> For the purpose of imparting flame retardancy, a flame retardant may be added to the adhesive composition of the present invention. There is no limitation on the flame retardant used in the present invention, but non-halogen is preferred for environmental awareness. As non-halogen flame retardants, there are also flame retardants such as nitrogen and metal hydroxide, but phosphorus flame retardants (E) are preferred from the viewpoint of excellent flame retardancy effect. As phosphorus flame retardants (E), there is no particular limitation as long as the structure contains phosphorus atoms, but from the viewpoints of hydrolysis resistance, heat resistance, low exudation, etc., phosphinic acid derivatives and phosphazene flame retardants are preferred. These can be used alone or in combination of two or more. The content of the flame retardant in the adhesive composition of the present invention preferably accounts for 1 to 50% by mass of the non-volatile components of the adhesive composition, and more preferably 10 to 40% by mass. When the content of the flame retardant is low, there is a situation where sufficient flame retardancy cannot be obtained. In addition, when the content of the flame retardant is high, there is a concern that the heat resistance, adhesion, and insulation reliability of the adhesive composition will decrease.

[0039] The phosphinic acid derivative is preferably a phenanthrene-type phosphinic acid derivative, and examples thereof include 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (manufactured by Sanko Co., Ltd., trade name: HCA), 10-benzyl-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide (manufactured by Sanko Co., Ltd., trade name: BCA), 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide (manufactured by Sanko Co., Ltd., trade name: HCA-HQ), and XZ-92741 manufactured by Olin.

[0040] The phosphazene flame retardant is represented by the following general formula (1) or (2) (wherein X is the same or different and is hydrogen, hydroxyl, amino, alkyl, aryl, phenoxy, allyl, cyanophenoxy, hydroxyphenoxy, etc., and n is an integer of 3 to 25). [Chemistry 1]

[0041] Commercially available products of these phosphazene flame retardants include, for example, phenoxy cyclophosphazene (manufactured by Otsuka Chemical Co., Ltd., trade names: SPB-100, SPE-100), cyanophenoxy cyclophosphazene (manufactured by Fushimi Pharmaceutical Co., Ltd., trade name: FP-300), and hydroxyphenoxy cyclophosphazene (manufactured by Otsuka Chemical Co., Ltd., trade name: SPH-100).

[0042] As the phosphorus flame retardant (E), it is preferred to use in combination (i) a phosphorus flame retardant having no functional group reactive with an epoxy group and (ii) a phosphorus flame retardant having a functional group reactive with an epoxy group, particularly a phosphorus flame retardant having two or more functional groups reactive with an epoxy group. The ratio of the phosphorus flame retardants (i) to (ii) is preferably 1:9 to 9:1, more preferably 2:8 to 8:2, in terms of mass ratio. When the amount of the phosphorus flame retardant (i) is too much, there is a concern that the insulation reliability may be reduced, and when the amount of the phosphorus flame retardant (ii) is too much, there is a possibility that the adhesion may be reduced.

[0043] For (i) phosphorus-based flame retardants that do not have a functional group that can react with an epoxy group, since they do not enter the cross-linked structure during thermal curing, they have the effect of giving flexibility to the adhesive after thermal curing. For example, the above-mentioned phenoxy cyclophosphazene (manufactured by Otsuka Chemical Co., Ltd., trade name: SPB-100, SPE-100), cyanophenoxy cyclophosphazene (manufactured by Fushimi Pharmaceutical Co., Ltd., trade name: FP-300), 10-benzyl-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide (manufactured by Sanko Co., Ltd., trade name: BCA), phosphate system (manufactured by Daihachi Chemical, trade name: PX-200) and the like belong to this category. For (ii) phosphorus-based flame retardants that have a functional group that can react with an epoxy group, since they enter the cross-linked structure during thermal curing, they have the effect of suppressing bleed out without reducing heat resistance. For example, the above-mentioned hydroxyphenoxy cyclophosphazene (manufactured by Otsuka Chemical Co., Ltd., trade name: SPH-100), 10-(2,5-dihydroxyphenyl)-10-H-9-oxa-10-phosphaphenanthrene-10-oxide (manufactured by Sanko Co., Ltd., trade name HCA-HQ), Olin XZ-92741, etc. belong to this category. Among them, for compounds having one functional group reactive with an epoxy group, since it becomes the end of the cross-linked structure and cuts off the cross-linked network, there is a possibility that the effect of not reducing heat resistance (ii) may become insufficient.

[0044] In addition to the above-mentioned phosphorus-based flame retardants, other phosphorus-based flame retardants may be used alone or in combination of two or more kinds as necessary, within the range not impairing flame retardancy, solder heat resistance, and low bleeding properties.

[0045] <Other ingredients> The adhesive composition of the present invention may contain a curing agent for further curing the epoxy resin (B) and a curing catalyst for accelerating the reaction between the epoxy resin (B) and the imide group-containing resin within a range that does not impair the properties. The curing agent is not particularly limited as long as it is a compound that can react with the epoxy resin (B), and examples thereof include amine curing agents, compounds having phenolic hydroxyl groups, compounds having carboxylic acids, compounds having acid anhydrides, and the like. These curing agents are used to adjust the functional group equivalents of the epoxy resin (B) and the imide group-containing resin.The curing catalyst is not particularly limited as long as it can promote the reaction of the epoxy resin (B) and the imide group-containing resin with the above-mentioned curing agent, and examples thereof include 2MZ, 2E4MZ, C11Z, C17Z, 2PZ, 1B2MZ, 2MZ-CN, 2E4MZ-CN, C11Z-CN, 2PZ-CN, 2PHZ-CN, 2MZ-CNS, 2E4MZ-CNS, 2PZ-CNS, 2MZ-AZINE, 2E4M ... Imidazole derivatives such as 4MZ-AZINE, C11Z-AZINE, 2MA-OK, 2P4MHZ, 2PHZ, 2P4BHZ, guanamines such as methylguanamine and benzoguanamine, diaminodiphenylmethane, metaphenylenediamine, metaphenylenediamine, diaminodiphenyl sulfone, dicyandiamide, urea, urea derivatives, melamine, polyhydrazides and other polyamines, organic acid salts and / or epoxy adducts thereof, amine complexes of boron trifluoride, ethyldiamino-S-triazine, 2,4-diamino-S-triazine, 2, Triazine derivatives such as 4-diamino-6-xylyl-S-triazine, trimethylamine, triethanolamine, N,N-dimethyloctylamine, N-benzyldimethylamine, pyridine, N-methylmorpholine, hexa(N-methyl)melamine, 2,4,6-tris(dimethylaminophenol), tetramethylguanidine, tertiary amines such as DBU (1,8-diazabicyclo[5,4,0]-7-undecene), DBN (1,5-diazabicyclo[4,3,0]-5-nonene), organic acid salts thereof and / or tetraphenylborate, Polyvinylphenol, polyvinylphenol bromide, organic phosphines such as tributylphosphine, triphenylphosphine, and tri-2-cyanoethylphosphine, quaternary phosphonium salts such as tri-n-butyl(2,5-dihydroxyphenyl)phosphonium bromide, hexadecyltributylphosphonium chloride, and tetraphenylphosphonium tetraphenylborate, quaternary ammonium salts such as benzyltrimethylammonium chloride and phenyltributylammonium chloride, the above-mentioned polycarboxylic acid anhydride, diphenyl iodonium tetrafluoroborate, triphenylsulfonium hexafluoroantimonate, 2,4,6-triphenylthiopyran hexafluorophosphate, photocationic polymerization catalysts such as Irgacure-261 (manufactured by Ciba Specialty Chemicals Co., Ltd.) and Optoma-SP-170 (manufactured by ADEKA Co., Ltd.), styrene-maleic anhydride resin, equimolar reactants of phenyl isocyanate and dimethylamine, equimolar reactants of organic polyisocyanates such as toluene diisocyanate and isophorone diisocyanate and dimethylamine, and the like. These curing agents and curing catalysts may be used alone or in combination of two or more.

[0046] In order to improve the adhesion, a silane coupling agent can be added to the adhesive composition of the present invention. As specific examples, aminosilane, mercaptosilane, vinylsilane, epoxysilane, methacrylsilane, isocyanatesilane, ketiminesilane or mixtures or reactants thereof, as well as compounds obtained by reaction of these with polyisocyanates, etc. As such silane coupling agents, for example, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylethyldiethoxysilane, bis(trimethoxysilylpropyl)amine, bis(triethoxysilylpropyl)amine, bismethoxydimethoxysilylpropylamine, bisethoxydiethoxysilylpropylamine, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2- Aminosilanes such as (aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylethyldiethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, γ-mercaptopropylmethyldimethoxysilane, γ-mercaptopropylmethyldiethoxysilane, γ-mercaptopropylethyldiethoxysilane, and other mercaptosilanes; vinyl Vinyl silanes such as trimethoxysilane, vinyl triethoxysilane, tri-(2-methoxyethoxy)vinyl silane, γ-glycidoxypropyl trimethoxysilane, γ-glycidoxypropyl dimethylethoxysilane, γ-glycidoxypropyl methyldiethoxysilane, β-(3,4-epoxycyclohexyl)ethyl methyldimethoxysilane, γ-glycidoxypropyl trimethoxysilane, β-(3,4-epoxycyclohexyl)ethyl trimethoxysilane The invention relates to methacryloyl silanes such as epoxy silane, 3-methacryloxypropyl methyl dimethoxy silane, 3-methacryloxypropyl trimethoxy silane, 3-methacryloxypropyl methyl diethoxy silane, 3-methacryloxypropyl triethoxy silane, isocyanate propyl triethoxy silane, isocyanate propyl silanes such as isocyanate propyl trimethoxy silane, ketone imide propyl trimethoxy silane, ketone imide propyl triethoxy silane and other ketone imine silanes. These can be used alone or in combination with more than two kinds. Among these silane coupling agents, since epoxy silane has a reactive epoxy group, it can react with an imide-containing resin, so it is preferred from the viewpoint of improving heat resistance and moisture-heat resistance. When the non-volatile component of the resin composition is 100% by mass as a whole, the mixing amount of the silane coupling agent is preferably 0 to 3% by mass, and more preferably 0 to 2% by mass. When the blending amount exceeds the above range, heat resistance tends to decrease.

[0047] In order to improve the heat resistance of solder, an organic filler or an inorganic filler may be added to the adhesive composition of the present invention within the range that does not impair the effect of the present invention. As the organic filler, powders of polyimide, polyamide-imide, etc. as heat-resistant resins may be cited. In addition, as the inorganic filler, for example, silicon dioxide (SiO 2 ), aluminum oxide (Al 2 O 3 ), titanium oxide (TiO 2 ), Tantalum Oxide (Ta 2 O 5 )、ZrO 2 ), silicon nitride (Si 3 N 4 ), barium titanate (BaO·TiO 2 ), barium carbonate (BaCO 3 ), lead titanate (PbO·TiO 2 ), lead zirconate titanate (PZT), lead lanthanum zirconate titanate (PLZT), gallium oxide (Ga 2 O 3 )、spinel (MgO·Al 2 O 3 ), mullite (3Al 2 O 3 ·2SiO 2 )、cordierite (2MgO·2Al 2 O 3 5SiO 2 ), talc (3MgO·4SiO 2 ·H 2 O), aluminum titanate (TiO 2 -Al 2 O 3 ), yttria-containing zirconium oxide (Y 2 O 3 -ZrO 2 ), barium silicate (BaO·8SiO 2 ), boron nitride (BN), calcium carbonate (CaCO 3 ), calcium sulfate (CaSO 4 ), zinc oxide (ZnO), magnesium titanate (MgO·TiO 2 ), barium sulfate (BaSO 4), organic bentonite, clay, mica, aluminum hydroxide, magnesium hydroxide, metal phosphinate, etc. Among them, silicon dioxide is preferred from the perspective of improving the ease of dispersion and the effect of heat resistance. These can be used alone or in combination of two or more. In addition, the amount of these organic fillers and inorganic fillers added is preferably 1 to 30% by mass, and more preferably 3 to 15% by mass relative to the non-volatile components of the adhesive composition. When the amount of organic fillers and inorganic fillers added is too much, there is a concern that the adhesive coating film will become brittle, and when the amount added is too little, there is a concern that the effect of fully improving heat resistance cannot be obtained.

[0048] <Flexible Printed Circuit Board> The adhesive composition of the present invention is suitable for use in flexible printed wiring boards. As a member constituting a flexible printed wiring board, the adhesive composition of the present invention can be used for a copper-clad laminate, a coverlay film, and an adhesive sheet.

[0049] The copper-clad laminate of the present invention has a structure in which copper foil is bonded to at least one surface of an insulating plastic film via the adhesive composition of the present invention. The copper foil is not particularly limited, and rolled copper foil or electrolytic copper foil conventionally used for flexible printed wiring boards can be used.

[0050] The cover film of the present invention has a structure in which an adhesive layer composed of the adhesive composition of the present invention and an insulating plastic film are laminated, and in particular, has a structure of insulating plastic film / adhesive layer or insulating plastic film / adhesive layer / protective film. The insulating plastic film refers to a film having a thickness of 1 to 200 μm and made of plastics such as polyimide, polyamide-imide, polyethylene terephthalate, polyethylene naphthalate, liquid crystal polymer (LCP), fluororesin, polyphenylene sulfide, polyether sulfone, polyether ether ketone, aramid fiber, polycarbonate, polyarylate, etc., and a plurality of films selected from these may be laminated. There is no particular limitation on the protective film as long as it can be peeled off without damaging the properties of the adhesive. Examples include plastic films such as polyethylene, polypropylene, polyolefin, polyester, polymethylpentene, polyvinyl chloride, polyvinylidene fluoride, and polyphenylene sulfide, and films of these films coated with silicone, fluoride, or other release agents, paper laminated with these films, and paper impregnated or coated with a releasable resin.

[0051] The adhesive sheet of the present invention has a structure in which an adhesive layer composed of the adhesive composition of the present invention and a peelable protective film are laminated, and in particular, has a structure of protective film / adhesive layer or protective film / adhesive / protective film. In the adhesive layer, there is a case where an insulating plastic film layer is provided. The adhesive sheet can also be used for a multilayer printed substrate.

[0052] In any of the above uses, the adhesive composition of the present invention is applied to an insulating plastic film or copper foil with a solution as a substrate, and the solvent is dried, and then hot-pressed and heat-cured with an adherend. In addition, for the purpose of adjusting the fluidity of the adhesive during hot-pressing, there is also a case where the imide-containing resin and the curing agent are partially reacted after the solvent is dried. In addition, the state before hot-pressing is referred to as the B stage.

[0053] In any of the above-mentioned uses, it is preferred that heat resistance, adhesion, flexibility, insulation, and flame retardancy are required after thermal curing. In addition, in the cover layer film and the adhesive sheet, they are usually stored, cut, punched, etc. in the B stage state, and flexibility in the B stage state is required. On the other hand, in the copper clad laminate, hot pressing and thermal curing are usually performed immediately after the B stage state is formed, and the cover layer film and the adhesive sheet are not required to be flexible in the B stage state. The cover layer film and the adhesive sheet using the adhesive of the present invention have high fluidity in the B stage state and high insulation after thermal curing. The flexible printed wiring board using the adhesive can cope with fine pitch patterns with a circuit width and a circuit spacing of several μm to 20 μm. In addition, it can also be applied to a flexible printed wiring board facing the coil with a large ratio of circuit height to circuit width (aspect ratio) and a small circuit spacing. Example

[0054] The effects of the present invention will be demonstrated below by way of examples, but the present invention is not limited thereto. The property evaluations in the examples were performed by the following methods.

[0055] (Evaluation method of adhesiveness) The adhesive composition solution was applied to a polyimide film (Apical 12.5NPI manufactured by Kaneka) to a thickness of 20 μm after drying, and dried at 140°C for 3 minutes using a hot air dryer to obtain a sample in the B-stage state. The adhesive-coated surface in the B-stage state was overlapped with the shiny surface of a copper foil (BHY manufactured by JX Nippon Mining and Petrochemical Co., Ltd., thickness 18 μm), placed in a press, and heated from room temperature to 180°C for 60 minutes at 30 kg / cm 2 The samples after heat-compression bonding were peeled off in a 180° direction at a speed of 50 mm / min using a tensile tester (manufactured by Shimadzu, Autograph AG-X plus) at 25°C to measure the bonding strength, and the adhesion was evaluated according to the following evaluation criteria. (Evaluation Criteria) ◎: Adhesion strength is 0.7N / mm or more ○: Adhesion strength is 0.5 N / mm or more and less than 0.7 N / mm ×: Adhesion strength is less than 0.5 N / mm

[0056] (Evaluation method of flame retardancy) The B-stage sample was prepared in the same manner as the adhesive evaluation method, and the adhesive-coated surface was heat-pressed to a polyimide film (Apical 12.5NPI manufactured by Kaneka) at 180°C for 60 minutes. The flame retardancy of the heat-pressed sample was evaluated based on the UL-94VTM standard according to the following evaluation criteria. (Evaluation Criteria) ○: Meets VTM-0 ×: Does not meet VTM-0

[0057] (Evaluation method of insulation reliability-1) The B-stage sample was prepared by the same method as the adhesive evaluation method, and thermally pressed at 180°C × 60 minutes on a polyimide printed circuit board with a comb-shaped circuit pattern formed using copper foil with a circuit width L and a circuit spacing S of L / S = 50μm / 50μm. Thereafter, a 50V voltage was applied for 1000 hours in an environment of a temperature of 85°C and a humidity of 85%, and the insulation reliability was evaluated according to the following evaluation criteria. (Evaluation Criteria) ○: The resistance value after 1000 hours is 5×10 8 Ω or above, no dendrites are generated ×: The resistance value after 1000 hours is less than 5×10 8 Ω or dendrites (Evaluation method of insulation reliability-2) Insulation reliability-2 is an evaluation method with stricter conditions for further reducing the L / S of the comb-type circuit pattern than insulation reliability-1. The B-stage sample was prepared in the same manner as the evaluation method of insulation reliability-1, and thermally pressed at 180°C × 60 minutes on a comb-shaped circuit pattern with L / S = 10μm / 10μm formed by a semi-additive method. Afterwards, a voltage of 50V was applied for 500 hours in an environment of temperature 85°C and humidity 85%, and the insulation reliability was evaluated according to the following evaluation criteria. (Evaluation Criteria) ◎: The resistance value after 500 hours is 1×10 8 Ω or more, no dendrites ○: The resistance value after 500 hours is 1×10 8 Ω or more but a small amount of dendrites are produced ×: Insulation breakdown after 500 hours

[0058] (Evaluation method of solder heat resistance) Samples after heat compression bonding were prepared in the same manner as the adhesive evaluation method, cut into 20 mm squares, and floated in a 280°C or 300°C solder bath with the polyimide film facing upward for 1 minute. Solder heat resistance was evaluated according to the following evaluation criteria. (Evaluation Criteria) ◎: No swelling or peeling occurred at either 280°C or 300°C ○: No swelling or peeling occurred at 280°C, but swelling or peeling occurred at 300°C ×: Bulging or peeling occurred at 280°C

[0059] (Production Example of Imide Group-Containing Resin (A1)) In a four-necked separable flask equipped with a stirrer, a cooling tube, a nitrogen inlet tube and a thermometer, 30 mol parts of trimellitic anhydride, 20 mol parts of BPADA, 50 mol parts of dimer acid, 100 mol parts of diphenylmethane diisocyanate and N-methyl-2-pyrrolidone as a polymerization solvent were added until the concentration of the decarburized resin component reached 40% by mass, and the temperature was raised to 100° C. under nitrogen to react for 2 hours, and further raised to 150° C. to react for 5 hours. Thereafter, cyclohexanone was added as a diluting solvent to dilute the mixture to a resin component concentration of 30% by mass, to obtain a solution of an imide group-containing resin (A1).

[0060] (Production Example of Imido Group-Containing Resins (A2) to (A12)) Solutions of imide group-containing resins (A2) to (A12) were prepared in the same manner as in the imide group-containing resin A1, except that the types and amounts of raw materials and solvents were changed to the resin compositions shown in Table 1.

[0061] The details of the raw materials used in Table 1 are as follows. Dimer acid: Croda manufactured PRIPOL1013 Hydrogenated dimer acid: Croda manufactured PRIPOL1009 BPADA: 4,4'-(4,4'-isopropylidene diphenoxy) diphthalic anhydride manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. ODPA: Oxydiphthalic anhydride manufactured by Tokyo Chemical Industry TMEG: Ethylene glycol bis(trimellitic anhydride) manufactured by Shin Nippon Rika Co., Ltd. TMPG: Trylead Chemical manufactures propylene glycol trimellitic anhydride TMA: Trimellitic anhydride manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. NBR: CTBN1300×13NA manufactured by HUNTSMAN, acrylonitrile-butadiene rubber with carboxyl groups at both ends MDI: Methylene diphenyl diisocyanate manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. TDI: Toluene diisocyanate manufactured by Tokyo Chemical Industry ToDI: Nippon Soda manufactures dimethyl biphenyl diisocyanate NMP: N-methyl-2-pyrrolidone manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. DMAc: N,N-dimethylacetamide manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.

[0062] [Table 1]

[0063] <Example 1> An adhesive composition was prepared by mixing a solution of an imide-containing resin (A1) having a solid content of 55 parts by mass, jER828 (epoxy resin (B) having a solid content of 25 parts by mass), BCA having a solid content of 10 parts by mass (phosphorus flame retardant (E)), and ZX-92741 having a solid content of 6 parts by mass (phosphorus flame retardant (E)). It should be noted that a dimethylacetamide solution having a solid content of 30% by mass was prepared in advance for use for jER828, BCA, and ZX-92741. The adhesive composition obtained was subjected to various evaluations of adhesion, flame retardancy, insulation reliability, and solder heat resistance. The results are shown in Table 2.

[0064] <Examples 2 to 13, Comparative Examples 1 to 3> The adhesive composition was prepared in the same manner as in Example 1 except that the types and amounts of the imide-containing resin (A), epoxy resin (B) and phosphorus-based flame retardant (E) were changed to the adhesive composition composition shown in Table 2. It should be noted that a dimethylacetamide solution having a solid content of 30% by mass was prepared in advance for the epoxy resin (B) and the phosphorus-based flame retardant (E). The adhesive composition obtained was subjected to various evaluations of adhesion, flame retardancy, insulation reliability and solder heat resistance. The results are shown in Table 2.

[0065] The details of the epoxy resin (B) and the phosphorus-based flame retardant (E) used in Table 2 are as follows. jER828: Epoxy resin manufactured by Mitsubishi Chemical (bisphenol type epoxy resin, epoxy equivalent 189 g / eq) jER152: Epoxy resin manufactured by Mitsubishi Chemical (phenol novolac type epoxy resin, epoxy equivalent 177 g / eq) jER1001: Epoxy resin manufactured by Mitsubishi Chemical (bisphenol type epoxy resin, epoxy equivalent 475 g / eq) BCA: 10-Benzyl-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide HCA: 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide ZX-92741: Olin, a phosphorus-containing phenolic compound with two phenolic hydroxyl groups

[0066] [Table 2]

[0067] As can be seen from Table 2, the adhesive compositions of Examples 1 to 13 that meet the necessary conditions of the present invention can simultaneously exhibit excellent adhesion, high insulation reliability and solder heat resistance. In contrast, in Comparative Example 1, since the imide-containing resin does not contain dimer acid as a structural unit, the flexibility of the adhesive is insufficient and the adhesion cannot be satisfied. In Comparative Example 2, since the imide-containing resin does not contain a dianhydride compound having an ester group or an ether group as a structural unit, the solder heat resistance deteriorates. In Comparative Example 3, since the imide-containing resin does not contain dimer acid as a structural unit, but uses acrylonitrile-butadiene rubber (NBR) as a raw material, the insulation reliability deteriorates due to the moisture absorption caused by the nitrile group in NBR. Industrial Applicability

[0068] The adhesive composition of the present invention is excellent in adhesiveness, insulation reliability, and solder heat resistance, and is therefore suitable for coverlay films, adhesive sheets, copper-clad laminates, etc. Therefore, the present invention is extremely useful in this field.

Claims

1. An adhesive composition, characterized in that The invention contains an imide group-containing resin (A) and an epoxy resin (B), wherein the imide group-containing resin (A) contains a dianhydride compound (C) having an ester group or an ether group and a dimer acid (D) as structural units.

2. The adhesive composition according to claim 1, characterized in that The dianhydride compound (C) is alkylene glycol bis(trimellitic anhydride).

3. The adhesive composition according to claim 1, characterized in that The dianhydride compound (C) is 4,4'-(4,4'-isopropylidene diphenoxy) diphthalic anhydride or oxydiphthalic anhydride.

4. The adhesive composition according to any one of claims 1 to 3, characterized in that The copolymerization amounts of the dianhydride compound (C) and the dimer acid (D) are each in the range of 1 to 80 mol % based on 100 mol % of the total polycarboxylic acid component amount constituting the imide group-containing resin (A).

5. The adhesive composition according to any one of claims 1 to 3, characterized in that It further contains a phosphorus-based flame retardant (E).

6. A copper-clad laminate, characterized in that: A copper foil is laminated on at least one surface of an insulating plastic film via the adhesive composition according to any one of claims 1 to 3.

7. A covering film, characterized in that: The adhesive layer composed of the adhesive composition according to any one of claims 1 to 3 and an insulating plastic film are laminated.

8. An adhesive sheet, characterized in that: The adhesive layer composed of the adhesive composition according to any one of claims 1 to 3 and a peelable protective film are laminated.

9. A flexible printed circuit board, characterized in that: A layer comprising the adhesive composition according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Heat resistant resin composition, adhesive film using this and polyimide film with adhesive

    JP2005179513A